The effect of fluorine on supramolecular hydrogelation of 4-fluorobenzyl-capped diphenylalanine1. (2nd June 2015) - Wu, Fang-Yi; Hsu, Shu-Min; Cheng, Hsun; Hsu, Ling-Huang; Lin, Hsin-Chieh
<x xml:space="preserve">Abstract</x> Due to the replacement of only one hydrogen atom by fluorine, 4-fluorobenzyl-diphenylalanine molecules self-assemble to form a transparent hydrogel.